T Regulatory Cells in Bone Remodelling - Bozec, Aline; Zaiss, Mario (Current Osteoporosis Reports, 2017)
In this review, we present the role of regulatory T (Treg) cells in bone remodelling and bone-related disease such as osteoporosis or inflammatory bone loss. We also discuss the cellular and molecular mechanism how Treg cells regulate osteoclastogenesis.Treg cells could regulate osteoclastogenesis by secreting TGF-? and IL-10 as well as IL-4 cytokines. Moreover, Treg cells can additionally regulate osteoclast differentiation, in a cell-to-cell contact via the cytotoxic T lymphocyte antigen (CTLA-4). The latter induces the apoptosis of osteoclasts dependent on CD80/86 in vitro and in vivo. Treg cells mediate immunosuppressive function that controls undesired immune reactions, such as autoimmunity. Recently, Treg cells have been shown to influence non-immunological processes, such as bone homeostasis. Accumulated evidences have demonstrated that Treg cells can suppress osteoclast differentiation in vitro and in vivo.
EVALuna2:13416